Rearing Enrichments Affected Ranging Behavior in Free-Range Laying Hens - Campbell, Dana L. M.; Dyall, Tim R.; Downing, Jeff A.; Cohen-Barnhouse, Andrew M.; Lee, Caroline (Frontiers in Veterinary Science, 2020)
Within Australia, free-range systems are prevalent, but pullets destined for range access are reared indoors. This mismatch between rearing and layer housing may hinder adaptation to the free-range environment. Rearing enrichment could enhance pullet development. A total of 1386 Hy-Line Brown® chicks were reared inside an experimental facility across 16 weeks with 3 enrichment treatments including 1) a control group with standard floor-housing, 2) a novelty group providing novel objects that changed weekly (‘novelty’ hens), and 3) a structural group with custom-designed H-shaped structures including opaque sides (‘structural’ hens). At 16 weeks of age all pullets were leg-banded with microchips and moved to an experimental free-range system with 9 identical pens (n = 3/rearing treatment). From 25 to 64 weeks, individual hen daily ranging behavior was tracked via radio-frequency identification technology and grouped into 6 age periods per rearing treatment. Video footage was used to count the number of hens at different distances on the range for the first 14 days of access and eggs were assessed for albumen corticosterone concentrations 4 days prior to (n = 450) and one week after first range access (n = 450). Across most age periods, the structural hens spent the most time ranging (P ≤ 0.01), the novelty hens showed the fewest number of visits to the range (P < 0.0001) and both enriched hen groups had the longest maximum visit durations (P ≤ 0.02). Range use increased with age across all treatments with only 3% of hens never going outside. All hens were initially slow to use the range area with fewer novelty hens venturing farther onto the range (P ≤ 0.03). The structural hens had higher albumen corticosterone concentrations and variance (both P ≤ 0.004) prior to range access. All hens showed an increase in albumen corticosterone following the first week of range access resulting in no differences between rearing treatments in means (P = 0.92) and variance (P = 0.63). Different enrichments have differing impacts on ranging behavior, but further research is needed to understand the mechanisms of effects, with differences in brain lateralization a potential hypothesis to be tested.